Analisis Perbedaan Penerapan Sekolah Ramah Anak dan Kompetensi Sosial Ditinjau dari Karakater Anak SD Negeri Kota Pekanbaru - Sardius, Sardius; Dewi Nasien; Amalia Sapriati (Journal for Lesson and Learning Studies, 2022)
The problem that occurs in schools, in general, is bullying. This problem needs to be addressed immediately so it does not become an increasingly worrying and ongoing problem. Ways to deal with violence by developing social skills. This study analyzes the differences in child-friendly school programs regarding character and social competence. This study uses quantitative analysis with comparative hypotheses to test the differences. The sample in this study was 352 children selected by proportional random sampling technique. The instrument in this study used a child-friendly school questionnaire, children's social competence, and children's character. Data analysis was performed using descriptive statistics and hypothesis testing using MANOVA. The data analysis results show differences in child-friendly school programs regarding children's character. Children with polite character have a very good perception of implementing the Child-Friendly School program. Second, there are differences in children's social competence in terms of the child's character. Children with polite character have very good social competence, while those with self-confidence and discipline have poor social competence results.